Students' Perceptions of Grading Practices and Impacts on Mindset Development - Julie Thiele (The Advocate, 2018)
This study examined the impact grading policies have on students’ mindsets in urban Midwestern middle schools. The components of this quasi-experimental, causal comparative survey research relied on the grading policies in place at the school level and the students’ reporting of their mindset. The findings demonstrated no statistically significant differences between the mindset levels of students from schools with different grading policies. Further analysis revealed inconsistencies between student perceptions of the grading practices and the schools’ stated grading policies. These findings begin to explore the impact grading practices have on students, during the transition from traditional to standards based grading.